DISKURSUS ILLAT, HIKMAH DAN SABAB SERTA KORELASINYA PADA KONSTRUKSI HUKUM ISLAM - Ahmad Arief; Darussalam Syamsuddin; Abdul Syatar (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2022)
This paper explores the basic concepts and correlations of illat, hikma and sabab, all three of which are terms that often intersect in the construction of Islamic law. exploring and contemplating the existence of the three concepts is very important to map out the basic differences between the three. Concept exploration uses library sources that are analyzed to obtain the basis for conceptual differences and explore the relationship between illat, hikma and sabab. The correlation between Illat, Wisdom and Sabab can be divided into two: first; the relationship between illat and sabab to wisdom, wisdom is complementary to both in providing a more philosophical construction of law, not just punishing. Second; The relationship between illat and sabab is complementary if you look at the generality and specificity of the two.